Prediction of gas hydrate formation conditions in Khangiran and Sarkhun gas fields in the presence of potassium chloride inhibitor - Sajjad Porgar; Somayeh Salehfekr; Mana Sakimehr (Journal of Chemistry Letters)
Gaseous hydrates are composed of light gases that are formed under certain temperature and pressure conditions. The formation of gas hydrate in the transmission lines causes clogging of the lines. To prevent the formation of gas hydrates, various solutions such as increasing the temperature, reducing the pressure and dehumidification can be mentioned and also using kinetic and chemical inhibitors. The aim of this study was to investigate the thermodynamic prediction of hydrate formation conditions of Khangiran and Sarkhun gas fields in Iran in the presence of KCl inhibitors and without inhibitors. The results were performed using Hydoff software and combining real percentages of gas fields. In order to validate them, the results were compared with experimental values. The results showed that with increasing temperature and also adding 5% potassium chloride inhibitor, gaseous hydrates are formed at higher pressures, and in order to predict the formation behavior of hydrates, mathematical models were presented for both cases.